PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SMART APPS CREATOR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Aulia, Fanesa; Zuryanty; Fitri, Ummiatul; Hamimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focuses on the suboptimal science learning, characterized by low student participation and difficulties comprehending the subject matter since grade IV primary school students have little access to interactive digital media that can illustrate the information on Indonesian Cultural Diversity. This study aims to create interactive educational materials using Smart Apps Creator. integrated with the Problem Based Learning model and to test its validity, practicality, and level of effectiveness. This study uses the ADDIE approach for development research (R&D). The research subjects include teachers and grade IV students at SDN 11 Indarung, SDN 21 Bandar Buat, and SDN 06 Padang Besi. Validation sheets, instructor and student response questionnaires, and learning outcome tests in the form of pretests and posttests were used to collect data.The data's outcomes analysis revealed that the smart apps creator media obtained a validity of 100% in terms of material, 95% in terms of media, and 91.17% in terms of language, with a 95.39% overall average which is included in the "very valid" criteria. The practicality level obtained an average teacher response of 99% and a student response of 88.33% which is classified as "very practical". In the effectiveness results, achieving an N-Gain of 65.21% shows that the media is seen "quite effective" in improving student learning outcomes. As a result, Smart Apps Creator-based interactive learning materials can be used to supplement IPAS instruction in grade IV elementary school.